2017
DOI: 10.1097/fbp.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin inhibits hippocampal NLRP3 inflammasome and exerts antidepressant effects in a chronic mild stress mice model

Abstract: A growing body of evidence suggests that inflammation may contribute toward the development of major depressive disorder. Mangiferin, a glucosylxanthone from Mangifera indica, exerts a number of biological actions, including anti-inflammatory effects. Although mangiferin has potential antidepressant activity, the mechanisms of this effect remain unclear. The present study investigated the effects of mangiferin on behavioral changes and inflammatory responses induced by chronic mild stress (CMS) in mice. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Similarly, inhibition of NO release was also reported for 2,4′,6-trihydroxy-4-methoxybenzophenone (25) (Pan et al 2016) which additionally showed DPPH radical scavenging effects (Pan et al 2016) as well as induction of apoptosis in HT-29 colon carcinoma cells (Lay et al 2014). Mangiferin (8), the main xanthone in I. adriatica rhizomes, revealed several activities related to antidiabetic effects, like inhibiting endothelial insulin resistance (Xu et al 2017) or α-glucosidase inhibition (Vo et al 2017) as well as anti-inflammatory and antidepressant action (Cao et al 2017). Irilone (34) was shown to possess α-amylase inhibitory effects which would support antidiabetic action (Ibrahim et al 2017).…”
Section: Quantitative Estimate Of Major Compounds In I Adriatica Rhimentioning
confidence: 78%
“…Similarly, inhibition of NO release was also reported for 2,4′,6-trihydroxy-4-methoxybenzophenone (25) (Pan et al 2016) which additionally showed DPPH radical scavenging effects (Pan et al 2016) as well as induction of apoptosis in HT-29 colon carcinoma cells (Lay et al 2014). Mangiferin (8), the main xanthone in I. adriatica rhizomes, revealed several activities related to antidiabetic effects, like inhibiting endothelial insulin resistance (Xu et al 2017) or α-glucosidase inhibition (Vo et al 2017) as well as anti-inflammatory and antidepressant action (Cao et al 2017). Irilone (34) was shown to possess α-amylase inhibitory effects which would support antidiabetic action (Ibrahim et al 2017).…”
Section: Quantitative Estimate Of Major Compounds In I Adriatica Rhimentioning
confidence: 78%
“…NLRP3 inflammasome, a multiprotein complex (cytosolic NLRP3, ASC, and cleaved caspace‐1), plays a crucial role in the maturation of pro‐inflammatory cytokines like IL‐1β and TNF‐α during psychological stress which contributes for the pathophysiology of depression (Cao et al, ; Iwata et al, ). Increased activation of NLRP3 inflammasome (protein expression) is detected in major depressive disorder patients as well as in various rodents in CMS model which results in upregulation of various pro‐inflammatory cytokines (Alcocer‐Gómez et al, ; Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased activation of NLRP3 inflammasome (protein expression) is detected in major depressive disorder patients as well as in various rodents in CMS model which results in upregulation of various pro‐inflammatory cytokines (Alcocer‐Gómez et al, ; Pan, Chen, Zhang, & Kong, ). Hence, any drug which might downregulate the expression of NLRP3 (activation) would be a potent therapeutic drug against depression (Cao et al, ). At present, numerous anti‐depressant drugs like selective serotonin reuptake, monoamine oxidase inhibitors, and tricyclic anti‐depressants are available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have determined that mangiferin protects against liver injury and endothelial dysfunction by inhibiting NLRP3 inflammasome activation in liver and endothelial cells 50,51 . Cao et al reported that mangiferin treatment repressed the expression of NLRP3, the adaptor protein ASC, and caspase‐1, thereby reducing the production of IL‐1β and IL‐18 in mice subject to chronic mild stress 52 . We analyzed the level of NLRP3 in LPS‐induced NSCLC cells and the secretion of IL‐1β in cell supernatants to examine if the anti‐inflammatory mechanism of mangiferin was influenced by NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%